(3OQGSI ebGQfIs - (3eMeO(B, (3eMeO GdZRGdjs ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2006)
(3eaghe GdEZQGb h CSHGHg h GgOGag h JGQjNg h ebOeGJ GdGZQGb h UhQg h GfhGYg h fWGbg h GdaQb Hjf GdGZQGb h CTHGgg cMQb GdGSYGQ h GdJSYjQ GdVGQj h Jdbj GdQcHGf h HjY GdhVYjI ceG Je GdJWQb Gdi GdGKGQ GdGbJUGOjI h GdGLJeGYjI ddGZQGb h Mceg aj dHTQjYI h aj GdfXe GdhVYjI h JfGhd GdeSFhdjI Yf GdGZQGb ceG Je GdJWQb Gdi JTQjYGJ ecGaMI GdGZQGb h GJaGbjI GdLGJ h ecGaMI GdGZQGb h GLgRI ecGaMJg (B.s
(3eQGLY U(B.424s
Keywords: (3GdEZQGbs; (3GdJShjbs